Sang Hyang Semara Ratih as The Creation of Painting - Ninggrat, I Dewa Gede Wisnu Jaya; Budiarta, I Dewa Putu Gede; Kondra, I Wayan (Program Studi Seni Murni ISI Bali, 2023)
This independent project thesis raises the title Sang Hyang Semara Ratih as the creation of a painting. In the Hindu mythological story Sang Hyang Semara Ratih, which is the lamp of the gods and goddesses as a symbol of love full of desire and loyalty and sacrifice. The story is told in Lontar Cundamani II. In this quote, it is told that heaven is being attacked by the giant Nilarudraka, a powerful giant who wants to rule over heaven. The gods were all defeated, none of them could fight him. Finally the gods came to Bhagawan Wraspati to ask and predict who would be able to beat the giant. Finally the results of the prediction showed that the giant Nilarudraka would only be defeated by the elephant-headed children of Lord Shiva. From the contents of this thesis, the author also reveals the creation of works of art, which the author creates and shows, namely the visuals of the Hindu Mythological object Sang Hyang Semara Ratih which contain many philosophical meanings in it. The conclusion of Sang Hyang Semara Ratih's thesis as the creation of this painting aims to provide an understanding for readers to recognize the meaning of the symbols contained in Sang Hyang Semara Ratih.